Development of Pop-Up Book Media to Improve Reading Skills of Grade II Elementary Schools - Bintang Khoironi; Ali Sunarso (Universitas Negeri Malang, 2025)
Abstract: Limited use of learning media can result in low reading abilities of students, especially in lower grades. The aim of this research is to produce and develop a Pop-Up Book learning media that is valid and suitable for use to improve reading skills. This research is a type of R&D (Research and Development) research or what is usually called development research using the ADDIE model. ADDIE has five stages: analysis, design, development, implementation, and evaluation. Data obtained from validation questionnaires. The research subjects involved 20 class II students at SDN 05 Pegundan, class teachers and validation from material and media experts. The data analysis techniques used are normality test, N gain test and t test. The validation results by media experts obtained a percentage of 92 percent (very feasible) while the validation results by material experts obtained a percentage of 94 percent (very feasible). The results of the pre-test and post-test evaluation show that there are significant differences. So it can be concluded that the research results from Pop-Up Book media to improve students' reading skills are valid, feasible and effective for use in the learning process. Abstrak: Keterbatasan penggunaan media pembelajaran dapat mengakibatkan rendahnya kemampuan membaca peserta didik, terutama pada kelas rendah. Tujuan penelitian ini adalah untuk menghasilkan dan mengembangkan sebuah media pembelajaran Pop-Up Book yang valid dan layak digunakan untuk meningkatkan kemampuan membaca. Penelitian ini merupakan jenis penelitian R&D ( Research and Development ) atau biasa disebut dengan penelitian pengembangan dengan menggunakan model ADDIE. ADDIE memiliki lima tahapan : analisis, desain, pengembangan, implementasi, dan evaluasi. Data didapatkan dari angket validasi. Subjek penelitian melibatkan 20 siswa kelas II SDN 05 Pegundan, guru kelas dan validasi dari ahli materi dan media. Teknik analisis data yang digunakan berupa uji normalitas, uji N gain dan uji t. Hasil validasi oleh ahli media memperoleh presentase 92 persen (sangat layak) sedangkan hasil validasi oleh ahli materi memperoleh prsentase 94 persen (sangat layak). Hasil evaluasi pre-test dan post-test menunjukan adanya perbedaan yang signifikan. Maka dapat disimpulkan bahwa hasil penelitian dari media Pop-Up Book untuk meningkatkan kemampuan membaca siswa valid, layak dan efektif digunakan dalam proses pembelajaran.